How to Train Your Dragon: Harnessing Gamma Delta T Cells Antiviral Functions and Trained Immunity in a Pandemic Era - Caron, Jonathan; Ridgley, Laura Alice; Bodman-Smith, Mark (Frontiers in Immunology, 2021)
The emergence of viruses with pandemic potential such as the SARS-CoV-2 coronavirus causing COVID-19 poses a global health challenge. There is remarkable progress in vaccine technology in response to this threat, but their design often overlooks the innate arm of immunity. Gamma Delta (γδ) T cells are a subset of T cells with unique features that gives them a key role in the innate immune response to a variety of homeostatic alterations, from cancer to microbial infections. In the context of viral infection, a growing body of evidence shows that γδ T cells are particularly equipped for early virus detection, which triggers their subsequent activation, expansion and the fast deployment of antiviral functions such as direct cytotoxic pathways, secretion of cytokines, recruitment and activation of other immune cells and mobilization of a trained immunity memory program. As such, γδ T cells represent an attractive target to stimulate for a rapid and effective resolution of viral infections. Here, we review the known aspects of γδ T cells that make them crucial component of the immune response to viruses, and the ways that their antiviral potential can be harnessed to prevent or treat viral infection.